An Extended Reinforcement Algorithm for Estimation of Human Behaviour in Congestion Games - Thorsten Chmura; Thomas Pitz (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
The paper reports simulations applied on two similar congestion games: the first is the classical minority game. The second one is a asymmetric variation of the minority game with linear payoff functions. For each game simulation results based on an extended reinforcement algorithm are compared with real experimental statistics. It is shown that the extension of the reinforcement model is essential for fitting the experimental data and estimating the players behaviour.
Keywords: C91; C92; C15; R4; 330; congestion game; minority game; laboratory experiments; reinforcement algorithm; payoff sum model